O lugar do ensino das ciências humanas no curso técnico em metalurgia do IFMG campus Ouro Preto (1944 a 2021) - Souza, Julio Cesar de (2023)
The central theme of this study is the importance of the teaching of Human Sciences in the Technical Course in Metallurgy at the Federal Institute of Minas Gerais – IFMG, Campus Ouro Preto, from 1944 to 2021. Methodologically our option was for a bibliographic research and a documentary study of records and transcripts of the Technical Course in Metallurgy at the IFMG Campus Ouro Preto. In order to understand this logic, based on documentary analysis, we have reconstructed the empirical elements that describe the curricula created by educational reforms, emphasising the place, role and social function of the teaching of Human Sciences and its consequences for the students’ integral human education. Based on the curriculum matrices, we found that from the point of view of the trajectory of the space occupied, over time, in the Human Sciences teaching curriculum, its workload increased as the Years progressed and curricular changes were made. We have thus established that the teaching of Human Sciences was limited within the curriculum design of the Technical Metallurgy Course and was the result of numerous disputes about the relevance of the training and the explicit justifications in the legislation of each phase. This place, where a range of content is taught, generally consisting of subjects such as History, Geography, Philosophy and Sociology, etc., is the result of a dispute that was both external in the teaching of general education with technical education and internal in the dispute between the assertion of the educational relevance of subjects in the teaching of science, the teaching of exact sciences (mathematics), the teaching of languages and the teaching of civics (OSPB and Moral and Civics). Gradually, the status of science education has been reshaped (in a nonlinear way), questioning its value as well as that of general education in three historical moments of regression : during the military dictatorship; during the FHC government; and with the current secondary education reform. However, it was reestablished in times of greater democracy and popular government with consequences both for access to higher education and for the training of technical professionals in the period of decline of the dictatorship and political opening, as well as in the Lula-Dilma governments.In summary, the research has shown that the comings and goings of educational reforms, reflected in political projects and legislative changes, generate mediations and contradictions that, over time, tend to reform the curricular organization in the federal network, especially in the group of Federal Institutes (IFs) that serve a specific educational project of human development.The teaching of Human Sciences fulfils a fundamental social mediation function for integral human education, as it provides a critical reading of the world of the graduates of the Integrated Technical Course in Metallurgy at IFMG Campus Ouro Preto. In other words, the teaching of Human Sciences is and must be a mandatory part of a curriculum that proposes a Polytechnic whose only school is for all classes and whose objective is an all-round education.